New and little known species of Eumolpinae (Coleoptera: Chrysomelidae) from Northern Vietnam - Romantsov, Pavel V.; Moseyko, Alexey G. (Zootaxa, 2019)
Three species (Demotina sapensis sp. nov., Parascela filimonovi sp. nov., Colaspoides pseudofemoralis sp. nov.) are described as new to science. A key to the species of Parascela and partial key to the species of Demotina are given. Color photographs of the habitus and of both male and female genitalia are presented. New synonymies and generic transfers are proposed: Leprotes rufonotatus Pic, 1924 is resurrected as a distinct species and transferred to the genus Demotina as Demotina rufonotata (comb. and stat. nov); Parascela tuberosa (Jacoby, 1887) (comb. nov) and Parascela rugipennis (Tan, 1988) (comb. nov) are transferred from the genus Basilepta; Parascela tuberosa Tan & Wang, 1983 is a new synonym of Parascela rugipennis (Tan, 1988) because of homonymy with Parascela tuberosa (Jacoby, 1887). Clisiterella Chen, 1940 is resurrected from synonyms of Iphimoides Jacoby, 1883 and considered as its subgenus. Iphimoides (Clisitherella) suturalis (Pic, 1928) (stat.nov.) is resurrected from synonyms of I. pallidulus (Jacoby, 1889) and transferred to subgenus Clisitherella, and the following names are considered as its synonyms: Clisitherella fukienensis Tan, 1983 (syn. nov), Clisitherella suturalis Chen, 1940 (syn. nov.), Iphimoides cheni L. Medvedev, 2001 (syn. nov.).